Individual variability in the migratory path and stopovers of a long-distance pelagic migrant - Dias, Maria P. (2013)
The analysis of repeated journeys of the same individuals is becoming an important tool in the study of animal migration. This approach has been used to analyse the migratory consistency (in schedules, routes and stopovers) of various species, with implications for the understanding of navigation mechanisms, travel strategies and conservation. However, few studies have addressed the individual consistency in pelagic long-distance migrations, in particular in the routes followed in different years. By analysing 100 journeys from 35 individual Cory’s shearwaters, Calonectris diomedea, that repeatedly migrated to the South African region we examined the fidelity to migratory paths and stopovers of a transequatorial seabird migrant. Cory’s shearwaters showed an overall trend to be faithful to their routes in different years, which was particularly obvious in the first (southbound) part of the outward migration. Nevertheless, we did not detect any individual consistency in the final part of the outward migration, in the return migration or in the location of the stopovers. The fact that Cory’s shearwaters can be either consistent or inconsistent in different parts of their routes is possibly related to the variability of the external factors (such as wind conditions and location of good foraging areas) found along the way. 2013 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.